2020
DOI: 10.1111/jvim.15873
|View full text |Cite
|
Sign up to set email alerts
|

Work, life, and the gender effect: Perspectives of ACVIM Diplomates in 2017. Part 2—The intersection of personal life and professional career

Abstract: Background: In the field of veterinary surgery, women neither marry nor have children at the same rate as men, and those who do may experience more career disruption as a result. The American College of Veterinary Internal Medicine (ACVIM) is 1 of the few areas of specialized medicine that is predominantly female; it is unknown if such a demographic shift would produce a different environment for individuals cultivating their personal life. Hypothesis/Objectives: To report data regarding subjective and objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…For any individual who has a family or is planning to start one, the living wage requirement becomes disproportionally higher owing to considerations such as childcare and other costs. Recent studies 23,24,34 of the 2 largest specialty colleges, the American College of Veterinary Surgeons and the American College of Veterinary Internal Medicine, have demonstrated a lack of racial and ethnic diversity, a low rate of childbirth during postgraduate training, 35,36 and a gender discrepancy in residency applications. 37 Although myriad factors surely participate in these differences, it is likely that implicit economic bias is a contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…For any individual who has a family or is planning to start one, the living wage requirement becomes disproportionally higher owing to considerations such as childcare and other costs. Recent studies 23,24,34 of the 2 largest specialty colleges, the American College of Veterinary Surgeons and the American College of Veterinary Internal Medicine, have demonstrated a lack of racial and ethnic diversity, a low rate of childbirth during postgraduate training, 35,36 and a gender discrepancy in residency applications. 37 Although myriad factors surely participate in these differences, it is likely that implicit economic bias is a contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…The needs and experiences of a female-predominant workforce are likely to be different on professional and personal levels, including work hours, career decisions, income and advancement gaps, and requirements for pregnancy and family planning. 6,13,[16][17][18] The degree to which a working environment will need to adapt may change as the proportion of women in the workforce continues to grow.…”
Section: Discussionmentioning
confidence: 99%
“…Women may more strongly consider the interrelationship of work and time when determining career choice as compared with men. 30 Female veterinary specialists both experience and perceive a more negative interrelationship between family and career 16,17 ; those experiences have caused some women physicians to leave the field of surgical practice. 31,32 Another study revealed higher rates of entry of women into residency training programs in specialties that decreased their working hours and showed that hour requirements influenced directly influenced female doctor's career choices more than other factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations